Radiation-induced rectal leiomyosarcoma in a cervical cancer survivor: a case report - Sulejmani, Haris; Vasilevski, Filip; Krsteska, Blagica; Tanevska Zrmanovska, Aneta; Mitreski, Nenad; Nikolovski, Andrej (Oxford University Press (OUP), 2025)
Rectal leiomyosarcoma (LMS) is an exceptionally rare malignancy, representing ˂0.5% of all rectal cancers. Even more uncommon are the cases of radiation-induced LMS arising as an independent malignancy following pelvic radiotherapy. We report a case of a 56-year-old female patient with a history of high-grade large cell neuroendocrine cervical carcinoma treated 12 years earlier with radical hysterectomy and adjuvant chemoradiotherapy. The patient presented with rectal discomfort and altered bowel habits. A colonoscopy revealed a near-obstructing polypoid rectal mass, and a biopsy confirmed LMS. Surgical treatment via abdominoperineal resection with total mesorectal excision was performed. Adjuvant chemotherapy was conducted by an oncologist. Given the long latency period and absence of metastases, the tumor was stated as a radiation-induced primary malignancy. This case emphasizes the importance of awareness in cancer survivors previously treated with pelvic radiotherapy and highlights the critical role of surgery in the management of rectal LMS.
Keywords: rectum; leiomyosarcoma; radiation-induced; radiotherapy